PEMANFAATAN SLUDGE INSTALASI PENGOLAHAN AIR LIMBAH INDUSTRI PULP DAN KERTAS SEBAGAI BAHAN BAKU BIOETANOL - Rina S. Soetopo; Sri Purwati; Yusup Setiawan; Susi Sugesty (Center for Pulp and Paper, 2012)
Investigation on utilization of sludge waste from Wastewater Treatment Plant (WWTP) of pulp and paper mill for bioethanol feedstock in a batch system at laboratory scale has been carried out. Experiments were conducted in three phases, namely the hydrolysis process; the fermentation process by Saccharomyces cerevisiae and the simultaneous saccharification-fermentation experiments. Ethanol concentration produced was tested by the HPLC method. Results show that t primary sludge from paper mills made from virgin pulp (sludge A) and primary sludge from pulp and paper made from raw wood (sludge B) at a 2% total solids having potential as raw material for bioethanol. The optimum conditions of the hydrolysis process of sludge A and sludge B is obtained from the sludge solids content of 6%, with the addition of cellulase of 9 FPU/g cellulose and beta-glucosidase of 6.7 IU/FPU for the incubation time of 48 hours producing the reducing sugar content of 31.3% and 36.2% with the hydrolysis efficiency of 64% and 71% respectively. On the SSF process conditions at pH of 4.5, temperature of 28oC for 96 hours, the sludge substrate A can produce ethanol with the concentration of 3.45% and the process efficiency of 72.5% and the sludge substrate B can produce ethanol with the concentration of 2.89% and the process efficiency of 60.8%.Keywords: bioethanol, cellulase, hydrolysis, fermentation, Saccharomyces cerevisiae, sludge ABSTRAK Penelitian pemanfaatan sludge Instalasi Pengolahan Air Limbah (IPAL) industri pulp dan kertas untuk bahan baku bioetanol dengan sistem batch pada skala laboratorium telah dilakukan. Percobaan dilakukan dalam tiga tahapan yaitu proses hidrolisis dengan enzim; proses fermentasi dengan Saccharomyces cerevisiae dan proses sakarifikasi-fermentasi serentak (SFS) pada satu reaktor. Kadar etanol yang dihasilkan diuji dengan metode HPLC. Hasil percobaan menunjukkan bahwa dari 4 jenis sludge yang diteliti, sludge primer dari pabrik kertas berbahan baku virgin pulp (sludge A) dan dari pabrik pulp dan kertas berbahan baku kayu (sludge B) berpotensi sebagai bahan baku bioetanol. Kondisi optimum percobaan proses hidrolisis sludge A dan sludge B diperoleh dari perlakuan dengan kadar padatan 6%, dosis selulase 9 FPU/g selulosa; dosis beta glukosidase 6,7 IU/FPU dengan lama inkubasi 48 jam, masing-masing menghasilkan kadar gula pereduksi sebesar 31,3% dan 36,2% dengan efisiensi hidrolisis 64% dan 71%. Pada percobaan SFS dengan kondisi proses pH 4,5 pada suhu 28oC selama 96 jam, substrat sludge A dapat menghasilkan etanol sebesar 3,45% dengan efisiensi proses 72,5% dan substrat sludge B dapat menghasilkan etanol sebesar 2,89% dengan efisiensi proses 60,8%.Kata kunci: bioetanol, selulase, hidrolisis, fermentasi, Saccharomyces cerevisiae, sludge